The Role of Adversity Quotient and Family Support in Adolescents’ Psychological Well-Being - Vio Meiticha Risanli; Indah Dwi Cahya Izzati; Iin Yulianti (Psikoislamedia: Jurnal Psikologi, 2026)
Many adolescents experience stress due to academic demands at school, which affects their mental health and psychological well-being. Psychological well-being is influenced by various factors, both internal and external, such as adversity quotient and family support. This study aims to determine the relationship between adversity quotient and family support with psychological well-being in adolescents. The study used a quantitative correlation method on 171 students of SMP X with multiple regression analysis using JASP software. The research instrument consisted of three scales, namely the psychological well-being scale based on the theory of Ryff and Keyes (1995), the adversity quotient scale based on the theory of Stoltz (2005), and the family support scale developed by the researcher. The results show that adversity quotient (r = 0.494; ; p<0.05) and family support (r=0.270; p<0.05) have a positive and significant relationship with psychological well-being. In conclusion, these two variables contribute 43.3% to the psychological well-being of adolescents.